Pain and disability : clinical, behavioral, and public policy perspectives - Osterweis, Marian; Kleinman, Arthur; Mechanic, David, 1936- (National Academy Press, 1987)
Evaluating claims based on pain poses problems for the Social Security Administration (SSA) and other disability insurers. This volume covers the epidemiology and physiology of pain; psychosocial contributions to pain and illness behavior; promising ways of assessing and measuring chronic pain and dysfunction; and clinical aspects of prevention.
Keywords: Chronic pain -- Social aspects.; Chronic pain -- Government policy.; Chronic pain -- Economic aspects.; Disability evaluation.; Chronic pain.; Chronic diseases.; Pain.; Sick -- Psychology.; Chronic Disease; Disability Evaluation; Pain; Public Policy; Sick Role; Douleur chronique.; Invalidité -- Évaluation.; Douleur chronique -- Aspect social.; Douleur chronique -- Politique gouvernementale.; Douleur chronique -- Aspect économique.; Maladies chroniques.; Douleur.; Malades -- Psychologie.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; Sick -- Psychology; Chronic pain; Chronic diseases; Chronic pain -- Social aspects; Disability evaluation